G1-S4 or G2-S16 carbosilan dendrimer in combination with Platycodin D as a promising vaginal microbicide candidate with contraceptive activity - Ceña-Diez R (Dove Medical Press, 2019)
Rafael Ceña-Diez,1,2 Alba Martin-Moreno,1 F Javier de la Mata,2,3 Rafael Gómez-Ramirez,2,3 Eduardo Muñoz,4 Manuel Ardoy,5 Ma Ángeles Muñoz-Fernández1,2 1Immunology Section, Head Inmuno-Biology Molecular Laboratory, Gregorio Marañón University General Hospital, Gregorio Marañón Health Research Institute (IiSGM), Spanish HIV HGM BioBank, Madrid, Spain; 2Networking Research Center on Bioengineering, Biomaterials and Nanomedicine (CIBER-BBN), Madrid, Spain; 3Organic and Inorganic Chemistry Department, Alcalá University, Alcalá de Henares, Spain; 4Department of Cell Biology, Physiology and Immunology, Instituto Maimónides de Investigación Biomédicas de Córdoba (IMIBIC), Reina Sofía University Hospital, University of Córdoba, Córdoba, Spain; 5Human Reproduction Unit, Gregorio Marañon University General Hospital, Madrid, Spain Purpose: HIV-1 and herpes simplex virus type-2 (HSV-2) represent two of the most relevant sexually transmitted diseases (STDs) worldwide. Moreover, each year there are >200 million pregnancies worldwide, and more than half are unintended. Continued high rates of unintended pregnancies and spread of HIV-1 and HSV-2 require new approaches to address these problems. G1-S4 and G2-S16 dendrimers emerge as potential candidates for the development of a topical microbicide due to their safety and effectivity against HIV-1 and HSV-2 infection, both in vitro and in vivo. Our goal is to develop a dual topical microbicide to prevent the transmission of STDs and unintended pregnancies. Platycodin D (PD) was selected for its great spermicidal activity, topical application, and biocompatibility. Materials and methods: Toxicology and inhibitory profile of G1-S4/PD and G2-S16/PD were evaluated in vitro and in vivo. Spermicidal activity was assessed by a computer-assisted sperm analysis system (CASA). Results: G1-S4/PD and G2-S16/PD presented >95% of HIV-1 inhibition in TZM-bl cells and peripheral blood mononuclear cells. CASA assessment determined that 0.25 mM of PD with therapeutic concentrations of G1-S4 or G2-S16 was able to induce 100% immobilization of the sperm in 30 seconds. To evaluate the toxicity in vivo, a vaginal toxicity assay was performed in BALB/c mice. No significant changes or damage to the vaginal epithelium after 7 consecutive days of application were observed. Conclusion: Our data indicate that G1-S4/PD and G2-S16/PD combinations are promising candidates to be developed for vaginal microbicides with contraceptive activity. Keywords: topical microbicide, HIV-1, HSV-2, Platycodin D, G1-S4 dendrimer, G2-S16 dendrimer